(3GdQSGdI GdPgHjIs - (3Ydj Hf ehSi GdcGXe Hf LYaQ GdUGOb, CHh GdMSf, GdedbH HGdQVj,J (B203 (3g` s ((3YHOGdQMef Hf YHOGddg GdcQNj s)
(3ChdgG (B:s
(3CeG HYO aEfg hUd cJGH CejQ GdeDefjf ajeG CeQfi Hg ef Jhajbg Ydi eG jMJGL Cdjg eG LQHJg hSeYJg ai GdCWYeg hGdCTQHI hCNP GdCOhjI hGdaUO hGdMLGeI hGdMeGe hGdfhQI hGdHGg hZjQ Pdc s
(3BNQgG (B:s
(3hdh CUjH GddU Chd eGjSQb aYhbH de jYO dcGfJ YbhHJg CSgd hGdCehQ cdgG HjO Gddg YR hLd s
(3CdagG ddNdjaI GdeCehf GdYHGSjs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B250s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B101 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B316 s
Keywords: (3GdWHs